Increased Cadre Motivation Conducting Childbirth Referrals through Training with the DABA Method - Dhiana Setyorini; Intim Cahyono; Jenie Palupi; Nur Hasanah (Humanistic Network for Science and Technology (HNST), 2021)
One of the causes of high maternal mortality is delivery assistance provided by other than health workers or traditional healers. The way to reduce the bondage relationship is to increase the motivation of cadres to refer mothers to health workers. The DABA method is a modification or development of the SALT method (support, appreciate, learn, and transfer), is a method or technique for forming something, showing that a community has the ability to respond to every challenge including childbirth assistance. The maternal mortality rate is still high, the Inter-Census Population Survey data released by the Central Statistics Agency shows that there were 359 maternal deaths per 100,000 births in 2013. The purpose of this study was to analyze the motivation of cadres by empowering the DABA method for referral for delivery assistance by health workers in Jember Regency. Motivation is the reason that underlies an action done by an individual. The method used was quasi-experimental using 2 groups. This study used the non equivalent control group, pre test post test design. The population in this study were 2220 posyandu cadres in the working area of the health centers in the Jember District. The subjects of this study were 100 posyandu cadres in Jember district in 2019 who met the criteria. The sampling technique was carried out by simple random sampling by selecting from a list of names of cadres in each health center. There was differences (p-value = 0.021) of cadre motivation between treatment and control group. The cadre motivation of intervention group was higher than the control group for referral labor. Having high motivation means having very strong reasons to achieve what he wants by doing his current job. The cadre motivation of treatment group increased significantly, this happened because cadres trained through the DABA method were invited to achieve the dreams they had built, namely to reduce maternal and infant mortality. Training using the DABA method is able to increase the motivation of cadres to make a referral to mothers to give birth at a health service place, so training with the DABA method is highly recommended to increase motivation for certain groups to achieve certain goals. Keywords: cadre motivation; DABA method; childbirth referrals